2019
DOI: 10.1590/1679-78255382
|View full text |Cite
|
Sign up to set email alerts
|

Study of cracks in concrete target under deep penetration by a projectile

Abstract: A large number of cracks occur in concrete structure after projectile penetration. The study of crack distribution and propagation process is the basis of damage assessment, structural repair and high dynamic fracture mechanism. In this paper, wire saw cutting, X-ray computed tomography (X-CT) and mechanical property testing of damaged concrete were carried out on deep penetration targets. According to X-CT images of radial core samples in target and the mechanical properties of damaged concrete, the crack dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
(19 reference statements)
0
4
2
Order By: Relevance
“…This trend is theoretically reasonable because the static resistance is smaller than its dynamic counterpart, attributing to a larger comminuted area at _ r c ¼ 0. However, this differs with the actual damage distribution in an experimental study [27] that r p is observed to be reduced at the ballistic end. The experimental observation is reported to be caused by the vanished concrete tangential inertial constraints at the end of the penetration process [27].…”
Section: Influences Of Target Compressive Strengthcontrasting
confidence: 65%
See 4 more Smart Citations
“…This trend is theoretically reasonable because the static resistance is smaller than its dynamic counterpart, attributing to a larger comminuted area at _ r c ¼ 0. However, this differs with the actual damage distribution in an experimental study [27] that r p is observed to be reduced at the ballistic end. The experimental observation is reported to be caused by the vanished concrete tangential inertial constraints at the end of the penetration process [27].…”
Section: Influences Of Target Compressive Strengthcontrasting
confidence: 65%
“…However, this differs with the actual damage distribution in an experimental study [27] that r p is observed to be reduced at the ballistic end. The experimental observation is reported to be caused by the vanished concrete tangential inertial constraints at the end of the penetration process [27]. Nevertheless, since the target inertia term in Eq.…”
Section: Influences Of Target Compressive Strengthcontrasting
confidence: 65%
See 3 more Smart Citations